An analysis of perceptions and support for Windows 10 Home Edition update features. Issue 1 (12th December 2020) - Morris, Jason; Becker, Ingolf; Parkin, Simon
Abstract: Home computer users are regularly advised to install software updates to stay secure. Windows 10 Home Edition automatically downloads and installs updates, restarting the computer if needed. Automatic restarts can be managed through a number of features, such as 'active hours' (within which a computer will not restart to complete an update) or by setting a time for restart. Applications active prior to a restart can register with the operating system, to automatically restart once updates have been installed. This research investigates if the features Microsoft provides for managing updates on Windows 10 Home Edition are appropriate for computer owners. We build a model of Windows 10 update behaviour, identifying interaction points between update features and users. We contrast theory with reality in a survey with 93 Windows 10 Home users, capturing experiences and perceptions. While overall perceptions of updates were positive, the pattern of use of most participants was incompatible with the default 'active hours' settings (28% of participants knew of its existence). Participants were mostly unaware of quality (bug fix) updates, mostly perceiving that updates add features. Half of our participants reported unexpected restarts, while half also reported growing concern about the state of their device if an update took a long time. Those with previous negative update experiences had weaker beliefs about their ability to control updates than those who had not. To make the updates less disruptive, applications can request to be restarted by Windows after a reboot. Of the 47 commonly used applications which were tested, only two supported seamless continuation after a restart. Unsaved data were lost in 21 applications, and 14 appeared to rely on internal autosave features to capture unsaved data, but did not completely restore User Interface arrangements. We recommend that operating systems obtain explicit permission for restarts, consistently; there are opportunities for features such as active hours and update progress displays to learn from usage activity. At the same time, applications should be more resilient to restarts to reduce the burden on users to recover their activities.